High-salt organic wastewater electrocatalytic scale inhibition system based on co3o4 nanowire modified electrode and application

By using Co3O4 nanowire modified electrodes in the electrochemical treatment of high-salt organic wastewater, the electric field and ion migration are regulated, and scale formation is inhibited, thus solving the problem of electrode performance degradation caused by complex scale and achieving efficient scale inhibition and electrode stability.

CN123041663APending Publication Date: 2026-11-06CHONGQING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611418809.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

In the electrochemical treatment of high-salt organic wastewater, existing technologies result in composite scale layers covering the active sites of electrodes, leading to a decrease in pollutant removal rate, an increase in energy consumption, and a shortened electrode lifespan. Furthermore, existing scale inhibition methods suffer from problems such as reagent consumption and equipment corrosion.

Method used

The electrode was modified with Co3O4 nanowires. By growing nanowires with pointed structures on the electrode surface, the electric field and ion migration were controlled to suppress scale formation. The electrode was then prepared on a conductive substrate using hydrothermal and annealing processes.

Benefits of technology

It achieves reduced scale deposition, maintains high TOC removal rate and low charge transfer resistance, and improves electrode stability and service life without the need for additional chemical scale inhibitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123041663A_ABST
    Figure CN123041663A_ABST
Patent Text Reader

Abstract

This invention discloses an electrocatalytic scale inhibition system for high-salt organic wastewater based on a Co3O4 nanowire modified electrode and its application, belonging to the field of electrocatalytic wastewater treatment technology. The system includes an electrochemical reactor, a cathode, an anode, and a power source; the cathode is a Co3O4 nanowire modified electrode with a pointed structure grown on its surface. The Co3O4 nanowire modified electrode has a three-dimensional nanowire array structure and a pointed structure, which is beneficial for improving ion migration and charge transport processes at the electrode / wastewater interface, reducing the deposition of scale-forming substances on the cathode surface, and thus inhibiting the formation of scale on the cathode surface. This invention can achieve in-situ scale inhibition during electrochemical treatment without adding or reducing the addition of chemical scale inhibitors. After multiple cycles of treatment, the system still maintains a high TOC removal rate and exhibits a low charge transfer resistance growth rate, with no thick scale layer forming on the electrode surface, making it suitable for the electrocatalytic treatment of high-salt organic wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrocatalytic wastewater treatment technology, specifically relating to an electrocatalytic scale inhibition system for high-salt organic wastewater based on a Co3O4 nanowire modified electrode and its application. Background Technology

[0002] High-salinity organic wastewater typically contains high concentrations of inorganic salts, hardness ions, and dissolved organic matter. Examples include oil and gas field backflow water, produced water, reverse osmosis concentrate, circulating cooling water, and some industrial wastewater. 2+ Mg 2+ Ba 2+ 、Sr 2+ HCO3 - CO3 2- SO4 2- It also contains humic acids, fulvic acids, and oily organic matter. During the electrochemical treatment process, the hydrogen evolution reaction at the cathode can lead to the presence of OH groups at the electrode interface. - Increased concentration and local pH levels induce the formation of inorganic crystal nuclei such as carbonates, hydroxides, and sulfates. Meanwhile, organic matter in wastewater can adsorb, complex, or coat inorganic crystals, causing the scale layer to further develop into an organic-inorganic composite scale.

[0003] This type of complex scale can cover the active sites of electrodes, block the three-dimensional electrode pore structure, and increase mass transfer resistance and charge transfer resistance, leading to a decrease in pollutant removal rate, an increase in energy consumption, and a shortened electrode life. Existing scale inhibition methods mainly include adding scale inhibitors, acid washing, backwashing, periodic electrode reversal, or mechanical cleaning, but these methods may have problems such as reagent consumption, secondary pollution, operation interruption, equipment corrosion, or high maintenance costs.

[0004] Existing studies have focused on mitigating electrochemical scaling by regulating electric fields or electrode structures, but there is still a lack of targeted material application solutions for complex scale formed by the joint participation of inorganic ions and organic matter in high-salt organic wastewater, as well as the impact of scale inhibition processes on the stability of organic matter electrochemical removal. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and to provide an electrocatalytic scale inhibition system for high-salt organic wastewater based on Co3O4 nanowire modified electrodes and its application.

[0006] The specific technical solution adopted in this invention is as follows:

[0007] In a first aspect, the present invention provides an electrocatalytic scale inhibition system for high-salt organic wastewater based on a Co3O4 nanowire modified electrode, comprising an electrochemical reactor, a cathode, an anode, and a power source; the cathode is a Co3O4 nanowire modified electrode with a pointed structure grown on its surface; the power source is connected between the cathode and the anode to apply an electric field; the electrochemical reactor is used to hold the high-salt organic wastewater to be treated, and under the action of the electric field, the pointed structure of the Co3O4 nanowire modified electrode forms a locally enhanced electric field, regulating the OH- ions at the electrode / wastewater interface. - And / or the migration of scale-forming ions, thereby inhibiting the formation of scale on the cathode surface.

[0008] Preferably, the Co3O4 nanowire modified electrode has a tip curvature radius of 1–100 nm, a nanowire length of 0.1–20 μm, and a nanowire density of 0.1–100 nanowires / μm. 2 .

[0009] Preferably, the method for preparing the Co3O4 nanowire modified electrode is as follows:

[0010] The pretreated and cleaned conductive substrate is immersed in a precursor solution and subjected to a hydrothermal reaction to obtain an intermediate product; the precursor solution is a mixed solution containing cobalt salt, urea and ammonium fluoride; the cleaned intermediate product is annealed to obtain a Co3O4 nanowire modified electrode with a pointed structure.

[0011] Furthermore, the conductive substrate is made of porous conductive carbon-based material or metal-based porous conductive material; wherein the porous conductive carbon-based material includes graphite felt, carbon felt, carbon cloth, and carbon paper, and the metal-based porous conductive material includes nickel foam, titanium mesh, or stainless steel mesh.

[0012] Furthermore, the cobalt salt is a water-soluble cobalt salt, preferably one or more of cobalt nitrate, cobalt chloride, cobalt sulfate, and their hydrates.

[0013] Furthermore, the molar ratio of cobalt ions, urea, and ammonium fluoride in the precursor solution is 1:5:2.

[0014] Furthermore, the hydrothermal reaction is carried out in a sealed reactor at a temperature of 100℃~120℃ for 8~12 h; the annealing treatment is carried out in a muffle furnace at a temperature of 350℃~450℃ for 2~3 h.

[0015] Preferably, the high-salt organic wastewater is wastewater containing scale-forming cations and dissolved organic matter; the scale-forming cations include Ca. 2+ Mg 2+ Ba 2+ 、Sr 2+One or more of the following, wherein the soluble organic matter includes humic acid substances, fulvic acid substances, soluble microbial metabolites, aromatic protein substances, oil-containing organic matter, nitrogen-containing organic matter, or combinations thereof.

[0016] Preferably, the power supply is controlled at a current density of 50~150 mA / cm². 2 Electrocatalytic reactions are carried out under certain conditions.

[0017] Secondly, the present invention provides an application of the electrocatalytic scale inhibition system for high-salt organic wastewater based on Co3O4 nanowire modified electrodes described in the first aspect in the electrocatalytic treatment of wastewater.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] (1) In this invention, the modified Co3O4 nanowire electrode is used as the cathode in the electrochemical treatment process of high-salt organic wastewater. The electrode has a unique conical tip nanowire structure and three-dimensional array structure, which is beneficial to improve the ion migration and charge transport process at the electrode / wastewater interface, reduce the deposition of scale-forming substances on the cathode surface, and can achieve in-situ scale inhibition without adding or reducing the addition of chemical scale inhibitors.

[0020] (2) The Co3O4 nanowire modified electrode used in this invention can still maintain a high TOC removal rate after multiple cycles of treatment and exhibits a low charge transfer resistance growth rate, indicating that the electrode can reduce the adverse effects of scale coverage on electrocatalytic performance and interfacial charge transport, and has good operational stability.

[0021] (3) The Co3O4 nanowire modified electrode used in this invention is prepared by hydrothermal combined annealing process, which can grow uniformly and densely on graphite felt substrate. The preparation process is simple and has good repeatability, which is beneficial to the application of electrocatalytic treatment system for high-salt organic wastewater. Attached Figure Description

[0022] Figure 1 XRD pattern (a) and XPS characterization results (b) of the Co3O4 nanowire modified graphite felt electrode prepared in Example 1.

[0023] Figure 2 SEM image of the unmodified graphite felt substrate;

[0024] Figure 3 SEM images of the Co3O4 nanowire modified graphite felt electrode prepared in Example 1, where (a) to (c) are SEM images at magnifications of 10000, 20000 and 100000, respectively.

[0025] Figure 4This is a schematic diagram of the electrocatalytic treatment device used in Example 2;

[0026] Figure 5 The images show the three-dimensional morphology of different electrodes under different cycles in Example 2. (a) to (c) are the three-dimensional morphology images of the Co3O4 nanowire modified graphite felt electrode after 0, 1 and 10 cycles, respectively, and (d) to (f) are the three-dimensional morphology images of the unmodified graphite felt electrode after 0, 1 and 10 cycles, respectively.

[0027] Figure 6 This is a comparison chart of the TOC removal rate changes during the wastewater recycling process treated by different electrodes in Example 2;

[0028] Figure 7 The images show the electrochemical impedance spectroscopy (EIS) spectra before and after the cyclic reaction at different electrodes in Example 2.

[0029] Figure 8 This is a comparison graph showing the charge transfer resistance (Rct) values ​​and their growth rates before and after the cyclic reaction of different electrodes in Example 2. Detailed Implementation

[0030] The present invention will be further described and illustrated below with reference to the accompanying drawings and specific embodiments. The technical features of each embodiment of the present invention can be combined accordingly, provided that there is no mutual conflict.

[0031] Example 1

[0032] This embodiment provides a method for preparing a Co3O4 nanowire modified graphite felt electrode, as detailed below:

[0033] (1) The graphite felt substrate was ultrasonically treated in a 50% ethanol solution for 15 min, and then ultrasonically treated in deionized water for 15 min to remove impurities from the surface of the graphite felt substrate. After cleaning, it was dried in an oven at 105℃ for later use.

[0034] (2) Prepare a 100 mL precursor solution containing 7.0 mmol cobalt nitrate hexahydrate Co(NO3)2·6H2O, 35.0 mmol urea (CO(NH2)2) and 14.0 mmol ammonium fluoride (NH4F). Transfer 60 mL of the precursor solution to a 100 mL high-pressure reactor lined with polytetrafluoroethylene.

[0035] (3) The pretreated graphite felt substrate (2 cm × 2 cm × 5 mm) was vertically immersed in the precursor solution. The reaction vessel was sealed and placed in a 120°C drying oven for hydrothermal reaction for 10 h. After the reaction was completed, the sample was naturally cooled to room temperature. The sample was then removed and washed with deionized water until the washing water was clear and colorless to remove surface residues and obtain the intermediate product.

[0036] (4) The above intermediate product was placed in a muffle furnace and annealed at 400°C for 2 hours to obtain Co3O4 nanowire modified graphite felt electrode.

[0037] Figure 1 (a) and Figure 1 (b) are the XRD and XPS characterization results of the Co3O4 nanowire-modified graphite felt electrode prepared in this embodiment. Figure 1 The XRD pattern in (a) shows obvious diffraction peaks near 31.2°, 36.8°, 59.3°, and 65.2°, corresponding to the (220), (311), (511), and (440) crystal planes of the spinel-structured Co3O4, respectively. No obvious impurity peaks were observed, indicating that a Co3O4 crystalline phase has formed on the electrode surface prepared in this embodiment. The sharp peaks and flat baselines indicate that the Co3O4 crystals in the electrode prepared in this embodiment have high crystallinity and purity. Figure 1 In the fine XPS spectrum of Co 2p in (b), Co 2p can be resolved. 3 / 2 and Co 2p 1 / 2 Two main peaks, after Gaussian-Lorentz peak fitting, show Co 2+ and Co 3+ The coexistence indicates that the resulting product exhibits the typical mixed valence state characteristics of Co3O4.

[0038] Figure 2 The image shows an SEM image of an unmodified graphite felt substrate, revealing a smooth and clean fiber surface with interwoven carbon fibers forming a conductive network. Figure 3 SEM images of the Co3O4 nanowire-modified graphite felt electrode prepared in this embodiment are shown, where (a) to (c) correspond to SEM images at magnifications of 10000, 20000, and 100000, respectively. Figure 3 It is evident that the entire carbon fiber skeleton of the graphite felt substrate is enveloped by a dense layer of Co3O4 fibers, with no exposed areas, indicating that Co3O4 achieves a dense and uniform coverage on the carbon fiber surface. Under high magnification, the Co3O4 exhibits a typical nanowire morphology, growing radially approximately perpendicular to the substrate surface, forming a three-dimensional array structure resembling a nanowire forest. Compared to the roots, the nanowires show a distinct tapering trend along the growth direction, forming a pointed structure at the apex. This pointed structure provides a structural basis for reducing scale deposition on the electrode surface and improving mass transfer and charge transport at the electrode / wastewater interface.

[0039] Example 2

[0040] This embodiment provides a method for verifying the scale inhibition performance of Co3O4 nanowire-modified graphite felt electrodes, as detailed below:

[0041] (1) such as Figure 4 As shown, the electrocatalytic treatment device includes a 150 mL cylindrical borosilicate glass sealed electrolytic cell 2, an electrode clamp 1, a cathode 3, an anode 4, a stirring rotor 5, a magnetic stirrer 6, and a DC power supply 7. In this embodiment, the anode is a Ti / RuO2-IrO2 electrode with dimensions of 20 mm × 20 mm × 2 mm; the cathode of the experimental group uses a Co3O4 nanowire modified graphite felt electrode prepared in Example 1, and the control group uses an unmodified graphite felt substrate with dimensions of 20 mm × 20 mm × 5 mm.

[0042] (2) Place an appropriate amount of high-salt organic wastewater in the electrolytic cell, ensuring that the anode and cathode are completely submerged in the shale gas return water and that their relative positions are fixed. Turn on the magnetic stirrer and set the speed to 300 rpm to maintain uniform water quality. Connect the DC power supply and set the current density to 100 mA / cm³. 2 The current density is based on the cathode geometric area. Electrocatalytic treatment begins, and the reaction time is 3 hours. A total of 10 backflow drainage cycles are performed.

[0043] The high-salt organic wastewater used in this embodiment is shale gas backflow. This shale gas backflow is weakly acidic to near neutral, with a pH of 6.7±0.09, total dissolved solids (TDS) of 38850±705 mg / L, and total organic carbon (TOC) of 216.1±9.3 mg / L; the main scale-forming cations include Ca. 2+ Mg 2+ and Ba 2+ The concentrations were 125.7±4.0 mg / L, 77.7±5.8 mg / L, and 105.1±2.6 mg / L, respectively. These water quality results indicate that the backflow water exhibits high salinity, high organic matter concentration, and the coexistence of multiple scale-forming cations, making it suitable as a representative scale-prone water sample in the electrochemical treatment process of high-salt organic wastewater.

[0044] (3) Before and after electrocatalytic treatment and at different cycle numbers, the cathode surface was observed non-contactly in three dimensions using a white light interferometry (SWLI) system. The results are as follows: Figure 5 As shown, this system combines sub-nanometer thin film thickness testing results with three-dimensional measurement technology, enabling imaging of the same area of ​​a sample.

[0045] according to Figure 5It can be seen that the Co3O4-modified graphite felt electrode exhibits good scale inhibition effect: in the initial stage of the cycle reaction (C1), the color distribution on the electrode surface does not change significantly, and long strip-shaped green areas (corresponding to the uncovered fiber skeleton) are clearly visible, indicating that no significant scale deposition has occurred at this time. Even after 10 cycles, only fine, interwoven yellow-green areas appear on the electrode surface. Although the surface height increases slightly, the flatness decreases somewhat, and there is a distribution of small scale particles, the overall thickness does not change significantly, and the overall outline of the electrode remains clearly visible. In contrast, the unmodified graphite felt electrode is completely covered by a thick scale layer after 10 cycles, and its three-dimensional morphology changes significantly. In summary, within 10 cycles of backflow treatment, the Co3O4-modified graphite felt electrode prepared in this invention can effectively inhibit the formation of a thick scale layer.

[0046] (4) This embodiment also monitored the TOC removal rate of shale gas backflow water in the electrolytic cell at different cycle numbers, and the results are as follows: Figure 6 As shown.

[0047] according to Figure 6 It can be seen that with the increase of the number of cycles, the TOC removal rate of the control group (unmodified graphite felt electrode) dropped sharply from the initial 45.4% to 13.6%, with a relative decay rate as high as 70.1%. This is mainly due to the severe scaling covering the active sites on the electrode surface and increasing the charge transport resistance at the electrode / solution interface, resulting in a significant decrease in electrocatalytic performance. In contrast, the experimental group (Co3O4 nanowire modified graphite felt electrode) showed excellent stability: after the same number of cycles, its TOC removal rate only decreased from 65.4% to 52.4%, with a relative decay of only 20.4%. This indicates that the Co3O4 nanowire modified graphite felt electrode system can still efficiently degrade organic matter in 10 cycles, strongly supporting the excellent scale inhibition effect of this electrode.

[0048] (5) In this embodiment, the changes in interfacial charge transport performance of different electrodes before and after 10 cycles of reaction were evaluated by electrochemical impedance spectroscopy (EIS). The results are as follows: Figure 7 and Figure 8 As shown.

[0049] Depend on Figure 7 It can be seen that the impedance arc of the unmodified graphite felt electrode increases significantly after 10 cycles, indicating that the charge transport resistance at the electrode / solution interface increases significantly. In contrast, the impedance arc of the Co3O4 nanowire modified graphite felt electrode changes little before and after cycling, indicating that its interfacial charge transport performance remains good.

[0050] Depend on Figure 8The results show that the Rct value of the unmodified graphite felt electrode before cycling (C0) was 18.21 Ω, which increased to 58.63 Ω after 10 cycles (C10), representing a growth rate of 222.0%. This indicates that the scale layer formed on the electrode surface during cycling significantly hindered electron transport at the electrode / solution interface. In contrast, the Rct value of the Co3O4 nanowire modified graphite felt electrode only increased from 14.27 Ω before cycling to 18.75 Ω after 10 cycles, a growth rate of only 31.4%. These results demonstrate that the Co3O4 nanowire modified graphite felt electrode can maintain a low interfacial charge transfer resistance even after multiple cycles, indicating a lighter degree of scale deposition and good anti-fouling ability and electrochemical stability.

[0051] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the invention. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the invention. Therefore, all technical solutions obtained through equivalent substitution or transformation fall within the protection scope of the present invention.

Claims

1. A high-salt organic wastewater electrocatalytic scale inhibition system based on Co3O4 nanowire modified electrodes, characterized in that, It includes an electrochemical reactor, a cathode, an anode, and a power source; the cathode is a Co3O4 nanowire modified electrode with a pointed structure grown on its surface; The power source is connected between the cathode and the anode to apply an electric field. The electrochemical reactor is used to hold the high-salt organic wastewater to be treated. Under the action of the electric field, the tip structure of the Co3O4 nanowire modified electrode forms a locally enhanced electric field, which regulates the migration of OH- and / or scale-forming ions at the electrode / wastewater interface, thereby inhibiting the formation of scale on the cathode surface.

2. The electrocatalytic scale inhibition system for high-salt organic wastewater according to claim 1, characterized in that, The Co3O4 nanowire modified electrode has a tip curvature radius of 1–100 nm, a nanowire length of 0.1–20 μm, and a nanowire density of 0.1–100 nanowires / μm. 2 .

3. The electrocatalytic scale inhibition system for high-salt organic wastewater according to claim 1, characterized in that, The method for preparing the Co3O4 nanowire modified electrode is as follows: The pretreated and cleaned conductive substrate was immersed in the precursor solution and subjected to a hydrothermal reaction to obtain an intermediate product. The precursor solution is a mixed solution containing cobalt salt, urea and ammonium fluoride; the washed intermediate product is annealed to obtain a Co3O4 nanowire modified electrode with a pointed structure.

4. The electrocatalytic scale inhibition system for high-salt organic wastewater according to claim 3, characterized in that, The conductive substrate is made of porous conductive carbon-based material or metal-based porous conductive material; wherein the porous conductive carbon-based material includes graphite felt, carbon felt, carbon cloth, and carbon paper, and the metal-based porous conductive material includes nickel foam, titanium mesh, or stainless steel mesh.

5. The electrocatalytic scale inhibition system for high-salt organic wastewater according to claim 3, characterized in that, The cobalt salt is a water-soluble cobalt salt, and the water-soluble cobalt salt is one or more of cobalt nitrate, cobalt chloride, cobalt sulfate and their hydrates.

6. The electrocatalytic scale inhibition system for high-salt organic wastewater according to claim 3, characterized in that, The molar ratio of cobalt ions, urea, and ammonium fluoride in the precursor solution is 1:5:

2.

7. The electrocatalytic scale inhibition system for high-salt organic wastewater according to claim 3, characterized in that, The hydrothermal reaction is carried out in a sealed reactor at a temperature of 100℃~120℃ for 8~12 h; the annealing treatment is carried out in a muffle furnace at a temperature of 350℃~450℃ for 2~3 h.

8. The electrocatalytic scale inhibition system for high-salt organic wastewater according to claim 1, characterized in that, The high-salt organic wastewater contains scale-forming cations and dissolved organic matter; the scale-forming cations include Ca. 2+ Mg 2+ Ba 2+ 、Sr 2+ One or more of the following, wherein the soluble organic matter includes humic acid substances, fulvic acid substances, soluble microbial metabolites, aromatic protein substances, oil-containing organic matter, nitrogen-containing organic matter, or combinations thereof.

9. The electrocatalytic scale inhibition system for high-salt organic wastewater according to claim 1, characterized in that, The power supply is a constant current power supply, and the current density during the electrocatalytic reaction is 50–150 mA / cm². 2 The current density is measured in terms of the cathode geometry.

10. The application of the electrocatalytic scale inhibition system for high-salt organic wastewater according to any one of claims 1 to 9 in the electrocatalytic treatment of high-salt organic wastewater, characterized in that, It is used to inhibit the deposition of scale-forming substances on the cathode surface while electrocatalytically removing organic matter from wastewater.